A web based survey using fuzzy set model - Ayu, Media Anugerah; Md. Tap, Abu Osman; Ismail, Aisyah (2010)
Turksen and Wilson (1995) have laid a theoretical ground for the works using a fuzzy set model for preference prediction. A fuzzy set conjoint model has been developed by incorporating fuzzy measurement of evaluations into the vector preference model. Mohtar et. al (2008)have done a study that used a fuzzy set preference model which represent linguistic variables, which usually used in survey research, to estimate overall preferences of costumer satisfaction on services provided by a shopping mall. This study by Mohtar et. al (2008) showed that the model has worked well and produced good results. Thus, we can use this fuzzy model to analyse survey data, instead of using statistical methods.